Johanna Hofmann-Stirnemann the first female museum director in Germany - Köpnick, Gloria 1988-; Stamm, Rainer 1967- (2023)
In 1930, Germany’s first publicly appointed female museum director took office: Hanna Stirnemann took over as director of the Jena City Museum that year. As museum director, she was a pioneer in a profession that had been defined by men until then. This article traces her museum career, which took her from the Oldenburg State Museum to the Reussisches Heimatmuseum in Greiz and finally to the Jena City Museum. There, she quickly made a name for herself as a museum director and outstanding art historian with a fine sense for an innovative exhibition and event program. The article will also show what happened after Stirnemann was forced to resign from her post by the National Socialists in 1935. After the war, the politically ‘unencumbered’ art historian was rehabilitated as mayor of a small town as well as director of the Rudolstadt Castle Museum and acting director of the Goethe and Schiller Archives in Weimar. In order to escape the restrictive cultural policy of the GDR, she moved to West-Berlin in 1950.